Analisis Isi Pesan Motivasi Dalam Film STIP Dan Pensil - Wafi, Cholid; Harahap, Nursapia; Susanti, Neila (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
The purpose of this research is to find out how the motivational message contained in the movie Stip and Pencil. The theory used to explore this research is Abraham Maslaw's Motivation Needs Theory. The object of research in this study is the Stip and Pencil Movie produced by MD. Picture. The method used in this research is qualitative method. The analysis technique used is content analysis. The results of the research in this study are in the Stip and Pencil movie there are motivational messages contained therein, such as the motivation of the needs contained in the Stip and Pencil movie is very good for the audience because it can be a trigger and a spirit generator in living life, especially young people and teenagers. The motivational messages carried out by Aghi, Tony, Saras and Bubu are very clearly illustrated in the actions and activities they do. The spirit they show is also a benchmark and can be a reference for the audience and movie lovers.